Somatic genetic alterations in synchronous and metachronous low-grade serous tumours and high-grade carcinomas of the adnexa - Murali, Rajmohan (Histopathology, 2019)
AIMS: Low-grade serous carcinomas (LGSCs) and their precursor serous borderline tumours (SBTs) characteristically harbour mutations in BRAF, KRAS and NRAS but rarely in TP53, whereas high-grade serous carcinomas (HGSCs) are characterised by frequent TP53 mutations but rare BRAF, KRAS and NRAS mutations. In a small subset of cases, LGSCs and/or SBTs develop high-grade tumours including HGSCs and poorly differentiated carcinomas (PDCs). Here we sought to define the repertoire of somatic genetic alterations in low-grade serous tumours and synchronous or metachronous high-grade adnexal carcinomas. METHODS AND RESULTS: DNA extracted from five SBTs/LGSCs and synchronous or metachronous HGSCs/PDCs and matched normal tissue was subjected to massively-parallel sequencing targeting all exons and selected non-coding regions of 341 cancer-related genes. The low-grade and high-grade tumours from a given case were related, and shared mutations and copy number alterations. Progression from low-grade to high-grade lesions was observed, and involved acquisition of additional mutations and copy number alterations or shifts from subclonal to clonal mutations. Only two (a HGSC and a PDC) of the five high-grade tumours investigated harboured TP53 mutations, whereas NRAS and KRAS hotspot mutations were seen in two and one HGSCs, respectively. CONCLUSIONS: Our results suggest that progression from SBT to HGSC may take place in a subset of cases, and that at least some of the rare HGSCs lacking TP53 mutations may be derived from a low-grade serous precursor.